Analisis Yuridis Pertanggung Jawaban Pidana Pelaku Tindak Pidana Kecelakaan Lalu Lintas Yang Mengakibatkan Korban Meninggal Dunia Perspektif Hukum Positif dan Hukum Pidana Islam (Studi Pada Putusan Nomor :29/Pid.Sus/2020/Pt Pdg): Legal Analysis of Criminal Responsibility of Perpetrators of Traffic Accidents Resulting in Death of Victims from the Perspective of Positive Law and Islamic Criminal Law (Study on Decision Number: 29/Pid.Sus/2020/Pt Pdg) - Muhammad Nawafil; Muhammad Aenur Rosyid (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
The existence of an incident commonly known as a traffic accident or accident caused by a negligent motorbike reder, and causing the loss of person’s life, includes the application of criminal liability under Article 310 paragraph 4 of Law Number 22 of 2009 concerning Traffic and Transportation and combined with the application of Restorative Justice based on Article 54 and Article 70 of the provisions of Law Number 1 of 2023 of the Criminal Code. The research category is normative juridical with reference to literature or normative juridicial library research which is based on existing secondary data, into data in the form of primary law. For example, the approach to law number 22 of 2009 cocerning Road Traffic and Transportation. Article 310 paragraph 4. The results of the research concluded that 1. Regarding the decision of the panel of judges in Decision Number 29/PID.SUS/2020/PT PDG the panel of judges considered juridically Article 310 paragraph 4 of Law Number 22 of 2009 LLAJ, in accordance with the single indictment of the Public Prosecutor by imposing a lighter sentence than the demands of the Public Prosecutor 2. That the consideration of the Panl of Judges is not in accordance with the theory of Criminal Individualization because it does not see objective reasons in lightening things for the defendant, in the from of forgiveness from the victim’s family and the actions that carried out by the Defendant without any intention form the Defendant, the panel of judges should not apply Article 310 paragraph 4 of Law Number 22 of 2009 LLAJ, so that it is line with the implementation of legal reform using the Criminal Individualization theory approach with the application of Law No. 1 of 2023 Criminal Code 3 states that criminal acts in Islamic law are categorized as qatlu al-khata as a reference to mitigating circumstances, in the view of Islamic law it provides an alternative space for forgiveness with criminal individualization for perpetrators of criminal acts of negligence by cyclists motorbike that caused the victim to die, which is known in Islamic law as Tahkim as legal reform. Adanya suatu kejadian yang biasa dikenal dengan laka lantas atau kecelakaan dengan penyebabnya oleh pengendara motor yang lalai, dan berpenyebab hilangnya nyawa seseorang dengan memuat penerapan pertanggungjawaban pidana pasal 310 ayat 4 undangundang Nomor 22 Tahun 2009 Tentang Lalu lintas dan Angkutan dan dikombinasikan dengan penerapan Restorative Justice berdasarkan Pasal 54 dan Pasal 70 ketentuan Undang-undang Nomor 1 Tahun 2023 Kitab Undang- undang Hukum Pidana. Kategori penelitian ini adalah yuridis normatif dengan acuan pustaka atau Library research yuridis normatif yang berdasar pada data sekunder yang ada, kedalam data dalam bentuk hukum primer. Misal Pendekatan pada undang-undang nomor 22 tahun 2009 Tentang Lalu lintas dan Angkutan jalan. Pasal 310 ayat 4. Hasil dari penelitian disimpulkan bahwa 1. Terkait Putusan Majelis Hakim pada Putusan Nomor 29/PID.SUS/2020/PT PDG Majelis hakim mempertimbangkan secara Yuridis pada Pasal 310 ayat 4 Undang-undang Nomor 22 Tahun 2009 LLAJ, sesuai dengan Dakwaan tunggal Jaksa Penuntut Umum dengan menjatuhkan pidana lebih ringan dari pada tuntutan jaksa Penuntut Umum 2. Bahwa Pertimbangan Majelis Hakim tidak sesuai dengan teori Individualisasi Pidana karena tidak melihat alasan Objektif dalam hal yang meringankan bagi terdakwa, berupa pemaafan dari keluarga korban dan perbuatan yang dilakukan oleh Terdakwa tanpa adanya niat dari Terdakwa, seharusnya majelis hakim tidak menerapkan pasal 310 ayat 4 Undang-undang Nomor 22 Tahun 2009 LLAJ, agar sejalan dengan penerapan pembaruan hukum dengan pendekatan teori Individualisasi Pidana dengan penerapan UU No. 1 Tahun 2023 KUHP 3 bahwa tindak pidana dalam hukum Islam dikategorikan qatlu al-khata sebgai acuan hal yang meringankan, di dalam Pandangan Hukum Islam memberikan ruang alternatif Pemaafan dengan Individualisasi Pidana bagi Pelaku Tindak Pidana kelalaian Pengendara sepeda motor yang mengakibatkan korban meninggal Dunia, yang dikenal dalam hukum Islam dengan istilah Tahkim sebagai pembaruan Hukum.